2020
DOI: 10.1111/jcmm.15501
|View full text |Cite
|
Sign up to set email alerts
|

Sitagliptin improves functional recovery via GLP‐1R‐induced anti‐apoptosis and facilitation of axonal regeneration after spinal cord injury

Abstract: Axon growth and neuronal apoptosis are considered to be crucial therapeutic targets against spinal cord injury (SCI). Growing evidences have reported stimulation of glucagon‐like peptide‐1 (GLP‐1)/GLP‐1 receptor (GLP‐1R) signalling axis provides neuroprotection in experimental models of neurodegeneration disease. Endogenous GLP‐1 is rapidly degraded by dipeptidyl peptidase‐IV (DPP4), resulting in blocking of GLP‐1/GLP1R signalling process. Sitagliptin, a highly selective inhibitor of DPP4, has approved to have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 49 publications
1
24
0
Order By: Relevance
“…Our results demonstrated that TEN displayed great potential in alleviating NP in PSNT rats through a GLP-1R independent mechanism. Though several reports have shown the neuroprotective effects of TEN by the upregulation of GLP-1R in neurodegenerative diseases, our findings show that TEN can also induce antinociception and neuroprotection through GLP-1R independent mechanisms [29,[50][51][52][53][54].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Our results demonstrated that TEN displayed great potential in alleviating NP in PSNT rats through a GLP-1R independent mechanism. Though several reports have shown the neuroprotective effects of TEN by the upregulation of GLP-1R in neurodegenerative diseases, our findings show that TEN can also induce antinociception and neuroprotection through GLP-1R independent mechanisms [29,[50][51][52][53][54].…”
Section: Discussionmentioning
confidence: 67%
“…Exendin-4, a peptide agonist of GLP-1 attenuated pain-induced cognitive impairment through the alleviation of neuroinflammation in NP rats [ 28 ]. In addition, DPP-4i like sitagliptin and GLP-1 analog liraglutide are shown to induce axonal regrowth and locomotor functional repair through the restoration of spinal GLP-1R levels in SCI rats [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…AMPK is a critical sensor of energy status, which regulates cellular energy homeostasis [28]. Several studies have shown that activating AMPK could ameliorate in ammation by inhibiting the activation of NF-κB [13,14,29,30].Furthermore, it has been reported that AMPK could be activated as a downstream of GLP-1R,when GLP-1R is activated [10][11][12]31]. Stimulating GLP-1R using sitagliptin could facilitate axonal regeneration and locomotor functional repair after spinal cord injury via GLP-1R induced AMPK/PGC-1α signaling pathway activation [12].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that activating AMPK could ameliorate in ammation by inhibiting the activation of NF-κB [13,14,29,30].Furthermore, it has been reported that AMPK could be activated as a downstream of GLP-1R,when GLP-1R is activated [10][11][12]31]. Stimulating GLP-1R using sitagliptin could facilitate axonal regeneration and locomotor functional repair after spinal cord injury via GLP-1R induced AMPK/PGC-1α signaling pathway activation [12]. A certain study has demonstrated that GLP-1 may suppress hepatic fat accumulation and in ammatory response induced by nutrients via the activation of the AMPK pathway [31].In our study, we demonstrated that AMPK was suppressed; however, NF-κB was hyperactive in mice with memory de cits caused by neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation